ANALISIS PERTIMBANGAN HAKIM DALAM MENOLAK PERMOHONAN ISBAT NIKAH Nomor 0094/Pdt.P/2019/PA.Kab.Mlg. DI PENGADILAN AGAMA KABUPATEN MALANG - Moh Yajid Fauzi; Ach Faisol; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
AbstackThis article discusses about the analysis of judges' considerations in the case of marriage isbat application in Malang District Religious Court. Second, the analysis of decisions based on judges' considerations. The last is the impact of the decision perspective of the maslahat perspective on children. These problems arose as a result of the implementation of a marriage that was not registered at the Marriage Registrar of the Office of Religious Affairs and then submitted a marriage request to take care of the child's birth certificate. This can be demonstrated from the case of the petitioners in the copy of the judge's decision. This study uses a normative juridical method with a descriptive analysis research approach, namely by analyzing and presenting systematic facts contained in the marriage request case number 0094/Pdt.P/2019/PA.Kab.Mlg. the conclusion of this research is based on the considerations of judges article 2 and 9 the marriage carried out violated the Marriage Law and Shari'a law and in its decision the Judge rejected the petition submitted. As for the analysis of a positive legal perspective judges in terms of article 14 and article 50 section 1 of the constitution number 48 of 2009 concerning judicial authority. Keywords: Judge’s consideration, Marriage isbat, Marriage Law